2022
DOI: 10.14710/nmjn.v12i2.42122
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Competency and its Related Aspects in Professional Education among Nursing Students of Two Nursing Schools in Iran: A Comparative Study

Abstract: Background: The importance of patient safety competency in nursing students to enter the clinical environment has made continuous studies necessary. However, only few studies have been conducted to assess and compare patient safety competency and its related aspects among nursing students in various settings.Purpose: This study aimed to compare patient safety competency and its related aspects among undergraduate nursing students of two nursing schools.Methods: This descriptive comparative study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
1
1
Order By: Relevance
“…Among the dimensions of PS competence, nursing students had the least confidence in their learning in teamwork with other health professionals both in the classroom and in clinical learning. These results are consistent with previous findings in the studies of Ginsburg et al , 20 Tella et al , 42 Alquwez et al , 15 Hwang et al , 17 Amilia and Nurmalia 32 Farokhzadian et al , 31 Alidousti-Shahraki et al 29 and Torkaman et al . 10 This evidence shows that weak interprofessional cooperation can be considered a dark point in the current field of healthcare.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the dimensions of PS competence, nursing students had the least confidence in their learning in teamwork with other health professionals both in the classroom and in clinical learning. These results are consistent with previous findings in the studies of Ginsburg et al , 20 Tella et al , 42 Alquwez et al , 15 Hwang et al , 17 Amilia and Nurmalia 32 Farokhzadian et al , 31 Alidousti-Shahraki et al 29 and Torkaman et al . 10 This evidence shows that weak interprofessional cooperation can be considered a dark point in the current field of healthcare.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results showed that the students had more confidence in their learning conducted in clinical settings than in the classroom, which are consistent with the results obtained in studies by Ginsburg et al 20 and Halbach and Sullivan37 and show that the opportunities provided for learners to use the theoretical lessons learnt in the classroom in clinical settings can lead to their greater confidence in obtaining safety competencies. However, this finding is contradictory to findings in Indonesia,32 China12 and Iran29 31 as participants in these studies had more confidence in their learning in the classroom. It should be noted that academic education is organised to create theoretical preparations, while clinical education helps students to make appropriate decisions based on the knowledge they have learnt in the classroom 38.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Of the demographic data factors, the most significant was the year of study, with more studies showing that nursing students' perception of patient safety declined in higher years (e.g., Duhn et al, 2012, Lukewich et al, 2015. Of the factors related to clinical environment, adverse events were the most prevalent, with students who experienced adverse events rating the patient safety issues significantly higher (e.g., Farokhzadian et al, 2022Stevanin et al, 2015Steven et al, 2014). In the academic environment, a significant impact has been identified in the area of patient safety teaching (e.g., Kong et al, 2019;Lee and Dahinten, 2022;Torkaman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Internal consistency was used to determine its reliability, and Cronbach's alpha ranged from 0.76 to 0.86. 19,24…”
Section: Instrumentsmentioning
confidence: 99%